Midwinter Dry Spells Amplify Post‐Fire Snowpack Decline - Benjamin J. Hatchett; Arielle L. Koshkin; Kristen Guirguis; Karl Rittger; Anne W. Nolin; Anne Heggli; Alan M. Rhoades; Amy E. East; Erica R. Siirila‐Woodburn; W. Tyler Brandt; Alexander Gershunov; Kayden Haleakala (Geophysical Research Letters, 2023)
Abstract Increasing wildfire and declining snowpacks in mountain regions threaten water availability. We combine satellite‐based fire detections with snow seasonality classifications to examine fire activity in California's seasonal and ephemeral snow zones. We find a nearly tenfold increase in fire activity during 2020–2021 versus 2001–2019. Accumulation season broadband snow albedo declined 25%–71% at two burned sites (2021 and 2022) according to in‐situ data relative to un‐burned conditions, with greater declines associated with increased burn severity. By enhancing snowpack susceptibility to melt, both decreased snow albedo and canopy drove midwinter melt during a multi‐week dry spell in 2022. Despite similar meteorological conditions in December–February 2013 and 2022–linked to persistent high pressure weather regimes–minimal melt occurred in 2013. Post‐fire snowpack differences are confirmed with satellite measurements. With growing geographical overlap between wildfire and snow, our findings suggest California's snowpack is increasingly vulnerable to the compounding effects of dry spells and wildfire.